2016
DOI: 10.1177/0972150916631206
|View full text |Cite
|
Sign up to set email alerts
|

Work Passion: Construction of Reliable and Valid Measurement Scale in the Indian Context

Abstract: Today ‘work passion’ is highly sought-after human capability to overcome intensifying environmental challenges. In this paper, we develop and validate the measure of ‘work passion’ in India. Two separate studies were conducted in this regard. In Study 1, work passion scale was developed and exploratory factor analysis (EFA) was conducted to examine its factor structure and reliability. In Study 2, confirmatory factor analysis (CFA) was conducted and construct validity was examined through its convergent and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Central to their conceptualization of passion is a deep sense of longing that impacts behavior whether positive or negative. Social psychologists were later interested in the concept (Barrett et al, 2007) and began to study it as a trait (Baum and Locke, 2004) and a motivational construct offering cognitive, affective and behavioral components where individuals do something they like (affective), something that is significant to their lives (cognitive) and something they spend time doing (behavioral) it on a regular basis (Shane et al, 2012;Baum and Locke, 2004;Vallerand et al, 2003;Johri et al, 2016;Drnovsek et al, 2016). Such studies covered mostly romantic relationships and passion for sports, arts, etc.…”
Section: Concept Of Passionmentioning
confidence: 99%
“…Central to their conceptualization of passion is a deep sense of longing that impacts behavior whether positive or negative. Social psychologists were later interested in the concept (Barrett et al, 2007) and began to study it as a trait (Baum and Locke, 2004) and a motivational construct offering cognitive, affective and behavioral components where individuals do something they like (affective), something that is significant to their lives (cognitive) and something they spend time doing (behavioral) it on a regular basis (Shane et al, 2012;Baum and Locke, 2004;Vallerand et al, 2003;Johri et al, 2016;Drnovsek et al, 2016). Such studies covered mostly romantic relationships and passion for sports, arts, etc.…”
Section: Concept Of Passionmentioning
confidence: 99%
“…Work passion remains a popular topic in the literature concerning human resources and organizational behavior (Hagel III et al, 2010;Perttula, 2004;Carpentier, Mageau & Vallerand, 2012). Johri et al (2016) defined passion in the context of 'work', 'activities', and 'entrepreneurship'. The current study adds to it 'business relationship' as well, where business relationship implies the profitable relationship between the provider of a service or product and its buyer.…”
Section: Discussionmentioning
confidence: 99%
“…In social psychology, passion is a motivational construct that is domain-specific (Chen et al, 2009). Johri et al (2016) found that the concept of passion has been studied in three different contexts 1) in the context of work, 2) in the context of activities, and 3) in the context of entrepreneurship. Although work passion is relevant for people, it is not irrelevant for organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The Work Passion Scale developed by Johri, Misra, and Bhattacharjee (2016) was used to measure employees’ “work passion.” The scale comprises 17 items and measures (a) love for one’s job experienced through the feeling of joy and vitality at work, (b) sense of self-motivation to do one’s work, (c) seeing one’s identity in terms of work, and (d) willingness to learn and improve continuously. Sample items of the scale include the following: “I generally feel excited to go to my work” (work engagement), “I get my motivation from the work itself and not from the rewards for it” (self-motivation), “I feel a sense of belongingness with my work” (self-identity), and “I always attempt to find new and better ways of doing my work” (sense of learning).…”
Section: Methodsmentioning
confidence: 99%